Morphological evolution of two-dimensional porous hexagonal trimesic acid framework - Tothadi, Srinu; Koner, Kalipada; Dey, Kaushik; Addicoat, Matthew; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2020)
Hexagonal single crystal structure (Form II) of trimesic acid (TMA) has been isolated by dissolving the interpenetrated Form I of TMA in tetrahydrofuran. Form II (hexagonal) was converted to Form I (interpenetrated) at room temperature through some intermediate structures. A detailed time-dependent FESEM study shows that the external morphology of Form II (hexagonal) is a hollow hexagonal tube that mimics its crystal structure. The block-shaped (morphology) of Form I (interpenetrated) was converted to the hollow hexagonal tube through some intermediate morphologies which are corresponding to particular crystal structures. Here, we have established a strong correlation between crystal structures with the morphology. These hollow tubes have been employed for Rhodamine B dye adsorption studies and showed an uptake of 82%, much more significant than Form I (interpenetrated) (39%) due to the presence of a pore channel in the crystal structure.
Keywords: dye adsorption; hollow hexagonal rod; hydrogen-bonded organic framework; morphology evaluation; trimesic acid

Porous covalent organic nanotubes and their assembly in loops and toroids - Koner, Kalipada; Karak, Shayan; Kandambeth, Sharath; Karak, Suvendu; Thomas, Neethu; Leanza, Luigi; Perego, Claudio; Pesce, Luca; Capelli, Riccardo; Moun, Monika; Bhakar, Monika; Ajithkumar, Thalasseril G.; et al. (Nature Chemistry, 2022)
Carbon nanotubes, and synthetic organic nanotubes more generally, have in recent decades been widely explored for application in electronic devices, energy storage, catalysis and biosensors. Despite noteworthy progress made in the synthesis of nanotubular architectures with well-defined lengths and diameters, purely covalently bonded organic nanotubes have remained somewhat challenging to prepare. Here we report the synthesis of covalently bonded porous organic nanotubes (CONTs) by Schiff base reaction between a tetratopic amine-functionalized triptycene and a linear dialdehyde. The spatial orientation of the functional groups promotes the growth of the framework in one dimension, and the strong covalent bonds between carbon, nitrogen and oxygen impart the resulting CONTs with high thermal and chemical stability. Upon ultrasonication, the CONTs form intertwined structures that go on to coil and form toroidal superstructures. Computational studies give some insight into the effect of the solvent in this assembly process.

Viscoelastic covalent organic nanotube fabric via macroscopic entanglement - Koner, Kalipada; Das, Susobhan; Mohata, Shibani; Duong, Nghia Tuan; Nishiyama, Yusuke; Kandambeth, Sharath; Karak, Suvendu; Reddy, C. Malla; Banerjee, Rahul (Journal of the American Chemical Society, 2022)
Covalent organic nanotubes (CONTs) are one-dimensional porous frameworks constructed from organic building blocks via dynamic covalent chemistry. CONTs are synthesized as insoluble powder that restricts their potential applications. The judicious selection of 2,2'-bipyridine-5,5'-dicarbaldehyde and tetraaminotriptycene as building blocks for TAT-BPy CONTs has led to constructing flexible yet robust and self-standing fabric up to 3 mu m thickness. The TAT-BPy CONTs and TAT-BPy CONT fabric have been characterized by solid-state one-dimensional (1D) C-13 CP-MAS, two-dimensional (2D) C-13-H-1 correlation NMR, 2D H-1-H-1 DQ-SQ NMR, and 2D N-14-H-1 correlation NMR spectroscopy. The mechanism of fabric formation has been established by using high-resolution transmission electron microscopy and scanning electron microscopy techniques. The as-synthesized viscoelastic TAT-BPy CONT fabric exhibits high mechanical strength with a reduced modulus (E-r) of 8 (+/- 3) GPa and hardness (H) of 0.6 (+/- 0.3) GPa. Interestingly, the viscoelastic fabric shows time-dependent elastic depth recovery up to 50-70%.

Morphology tuning via linker modulation: metal-free covalent organic nanostructures with exceptional chemical stability for electrocatalytic water splitting - Karak, Shayan; Koner, Kalipada; Karmakar, Arun; Mohata, Shibani; Nishiyama, Yusuke; Duong, Nghia Tuan; Thomas, Neethu; Ajithkumar, Thalasseril Govindankuttykaimal; Hossain, Munshi Sahid; Bandyopadhyay, Subhajit; Kundu, Subrata; Banerjee, Rahul (Advanced Materials, 2024)
The development of synthetic routes for the formation of robust porous organic polymers (POPs) with well-defined nanoscale morphology is fundamentally significant for their practical applications. The thermodynamic characteristics that arise from reversible covalent bonding impart intrinsic chemical instability in the polymers, thereby impeding their overall potential. Herein, a unique strategy is reported to overcome the stability issue by designing robust imidazole-linked POPs via tandem reversible/irreversible bond formation. Incorporating inherent rigidity into the secondary building units leads to robust microporous polymeric nanostructures with hollow-spherical morphologies. An in-depth analysis by extensive solid-state NMR (1D and 2D) study on H-1, C-13, and N-14 nuclei elucidates the bonding and reveals the high purity of the newly designed imidazole-based POPs. The nitrogen-rich polymeric nanostructures are further used as metal-free electrocatalysts for water splitting. In particular, the rigid POPs show excellent catalytic activity toward the oxygen evolution reaction (OER) with long-term durability. Among them, the most efficient OER electrocatalyst (TAT-TFBE) requires 314 mV of overpotential to drive 10 mA cm(-2) current density, demonstrating its superiority over state-of-the-art catalysts (RuO2 and IrO2).
Keywords: bi-functional electrocatalysts; chemically robust; hollow-spherical morphologies; imidazole-linked; inherent rigidity; metal-free; water splitting